Phenotypic and molecular detection of Acinetobacter baumannii retrieved from the environmental surfaces - Beva, Homayra Zarin Noor (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.